Independent Learning Curriculum Innovation in Driving Schools in Basic Education - Hidayah, Nurul; Negara, Hasan Sastra; Kalifah, Diah Rizki Nur (STKIP PGRI Bandar Lampung, 2025)
To welcome the new curriculum, national education, especially basic education, requires independent learning innovation through driving schools. The purpose of this research is to find out the trends and publications of the independent learning curriculum in driving schools in basic education. The method used is qualitative with a bibliometric analysis approach. Documents collected from the Publish or Perish (PoP) application using the Google Scholar database are then combined into one file in RIS format and entered into the VOSviewer application. The results of the research show that there are 200 articles from the analysis over the last three years (2020-2023). In 2022, the largest number was obtained, namely 120 documents. The institution that published the most documents was Universitas Pahlawan Tuanku Tambusai with 23 documents and obtained 1082 citations. The publication with the most citations was written by Muhammad Rusli Baharuddin with the title